Understanding the binding mechanism for potential inhibition of SARS‐CoV‐2 Mpro and exploring the modes of ACE2 inhibition by hydroxychloroquine. Issue 2 (6th November 2021) - Choudhury, Manisha; Dhanabalan, Anantha K.; Goswami, Nabajyoti
Abstract: As per the World Health Organization report, around 226 844 344 confirmed positive cases and 4 666 334 deaths are reported till September 17, 2021 due to the recent viral outbreak. A novel coronavirus (severe acute respiratory syndrome coronavirus 2 [SARS‐CoV‐2]) is responsible for the associated coronavirus disease (COVID‐19), which causes serious or even fatal respiratory tract infection and yet no approved therapeutics or effective treatment is currently available to combat the outbreak. Due to the emergency, the drug repurposing approach is being explored for COVID‐19. In this study, we attempt to understand the potential mechanism and also the effect of the approved antiviral drugs against the SARS‐CoV‐2 main protease (Mpro). To understand the mechanism of inhibition of the malaria drug hydroxychloroquine (HCQ) against SARS‐CoV‐2, we performed molecular interaction studies. The studies revealed that HCQ docked at the active site of the Human ACE2 receptor as a possible way of inhibition. Our in silico analysis revealed that the three drugs Lopinavir, Ritonavir, and Remdesivir showed interaction with the active site residues of Mpro. During molecular dynamics simulation, based on the binding free energy contributions, Lopinavir showed better results than Ritonavir and Remdesivir.